IMPLEMENTASI PROGRAM TAHFIDZ ALQURAN DI SEKOLAH DASAR ISLAM AL AZHAR - Siregar, Yusnil Khoiriah; Martin Kustati; Rezki Amelia; Gusmirawati Gusmirawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to describe and examine the learning system of the tahfidz programme as well as the methods used by teachers in teaching the memorisation of the Koran in the tahfidz programme at SD Islam Al Azhar 32 Padang. This type of research is descriptive qualitative research. Data collection techniques are structured interviews and observation and documentation. Data analysis techniques are data reduction and data presentation and conclusion drawing. The research subjects were determined by purposive sampling technique. The results showed that the Quran memorising programme at Al Azhar Islamic Elementary School 32 Padang implements a holistic approach such as Quran memorisation, understanding, repetition and time discipline. Every element of the school is always committed to improving quality such as the existence of collaboration groups with parents, daily memorisation and murajaah schedules, daily evaluations to increase student independence in memorising the Koran and memorisation improvement and graduation exams. The method in teaching tahfidz is using the talaqqi, tahsin, murajaah and tasmi' methods. The implementation of this tahfidz programme is carried out in groups based on the level of ability and acceleration of memorisation in each class with three accompanying teachers. With this programme, it is expected to be able to create quality students.